A study of electroactive polyvinyl chloride (PVC) gel actuators through the use of the electric modulus formalism and cyclic linear voltage sweeps. (1st March 2022) - Frank, Zachary; Al-Rubaiai, Mohammed; Tan, Xiaobo; Kim, Kwang J
Abstract: The conductivity and dielectric properties are integral to the function of polyvinyl chloride (PVC) gel actuators. The frequency-dependent properties of PVC gel actuators are investigated here in terms of their impedance, permittivity, and for the first time, electric modulus. The data shows that PVC gels' conductive properties are just as, if not more, important as their dielectric properties in electromechanical transduction applications. The electrode polarization (EP) and its impact on the impedance and dielectric spectra of PVC gels, as well as the developed asymmetric space charge at the anode, are discussed. The electric modulus and tan δ spectra are used for the fitting of Cole-Cole (CC) and Debye relaxation models for gels of varying plasticizer content. The electrostatic adhesive force for PVC gels of varying plasticizer is also measured, indicating large electrostatic adhesion (>2 N cm −2 ). A cyclic linear voltage sweep is used to clarify the dynamics of space charge within the gels. The peak current (associated with space charge development) is seen to be concurrent with the onset of mechanical deformation, showing the asymmetric charge as the origin of electromechanical transduction. Additionally, the maximum charge transferred (as measured by the integration of current over time) before space charge development is found to correlate with the electrostatic adhesive force measured for the gels, pointing to a new method of characterizing PVC gels for actuation.